Don Quijote y los otros en el Ingenioso hidalgo - Muñoz Sánchez, Juan Ramón (El Colegio de México, 2026)
Throughout Don Quixote de la Mancha, Don Quixote and Sancho encounter characters in whom they see an image of themselves and who, reciprocally, see them as objects to be contemplated; characters in whom they glimpse traits of their own personality as well as notable contrasts, who help them to affirm their own identity, encourage them to modify their behavior, to probe other possible ways of developing and behaving, in short, to evolve psychologically. The present article aims to analyse this strategy in the construction of characters. It centers on the figure of Don Quixote as he is presented in the First Part, on his confrontations with the sly innkeeper, the courtly knight Vivaldo, Ginés de Pasamonte, Cardenio and the canon of Toledo.